2012
DOI: 10.1088/1748-6041/7/5/055009
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of positively charged poly(ethylene glycol)-diacrylate hydrogel as a bone tissue engineering scaffold

Abstract: To improve cell attachment and to understand the effects of positive charge on the behavior of osteoblasts, 2-(methacryloyloxy)ethyl-trimethylammonium chloride (MAETAC), a positively charged monomer, was incorporated into poly(ethylene glycol)-diacrylate (PEGDA) hydrogel. The physicochemical properties of the resultant polymers, including the degree of acrylation of PEGDA, pKa of MAETAC, swelling ratio, zeta potential, and protein adsorption were investigated. Meanwhile, osteoblast-like MC3T3-E1 cells were see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 44 publications
2
59
1
Order By: Relevance
“…An explanation was made in term of ion crowding in the electric double layer [43,44,45], whereby the crowding of counterions dominates screening. When KNN were immersed into cell culture medium, since most proteins are negatively charged under physiological conditions, as a result of an isoelectric point less than 6 [50,51], negative protein were selectively adsorbed on positive KNN surface, forming a protein layer that contributes to cell adhesion [52] (Figure 6a). While on negative KNN surface, cations including Ca 2+ counter-ions, which is considered to promote osteoblast cell adhesion by attracting negatively charged proteins from cell medium [16] and by supplying Ca 2+ to binding sites in transmembrane proteins responsible for cell adhesion and proliferation [53], were closely attracted, contributing to the adhesion and proliferation of cells on this surface (Figure 6b).…”
Section: Resultsmentioning
confidence: 99%
“…An explanation was made in term of ion crowding in the electric double layer [43,44,45], whereby the crowding of counterions dominates screening. When KNN were immersed into cell culture medium, since most proteins are negatively charged under physiological conditions, as a result of an isoelectric point less than 6 [50,51], negative protein were selectively adsorbed on positive KNN surface, forming a protein layer that contributes to cell adhesion [52] (Figure 6a). While on negative KNN surface, cations including Ca 2+ counter-ions, which is considered to promote osteoblast cell adhesion by attracting negatively charged proteins from cell medium [16] and by supplying Ca 2+ to binding sites in transmembrane proteins responsible for cell adhesion and proliferation [53], were closely attracted, contributing to the adhesion and proliferation of cells on this surface (Figure 6b).…”
Section: Resultsmentioning
confidence: 99%
“…Cell adhesion is a fundamental factor in the biomaterials field and is regulated by biological, biochemical and environmental factors. Previous findings have indicated that the surface charge of the biomaterial plays an important role in cell attachment and differentiation in chondrocytes and in bone tissue engineering . The mechanism by which the charges and piezoelectric properties affect the responses at this biological interface has been investigated; however, not a single mode of action has been identified to date.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative strategy for bridging large bone defects is the use of tissue engineering scaffolds, i.e., natural or synthetic scaffolds that can be seeded with osteogenic cells. For example, hard scaffold materials such as polycaprolactone (PCL) or hydroxyapatite can contribute to measurable bone repair (7,8), as can "soft" scaffolds composed of natural or synthetic products (7,8). Among the many choices of soft natural biomaterials for bone tissue engineering, type I collagen is popular as it is abundant and is the primary organic component of bone matrix (9).…”
Section: Introductionmentioning
confidence: 99%